Use of recombinant tissue plasminogen activator for treatment of recalcitrant anterior uveitis: A case series. Issue 5 (October 2018) - Patrick, Sylves; Hui-Tze, Chan; Wan-Hazabbah, Wan Hitam; Zunaina, Embong; Azhany, Yaakub; Liza-Sharmini, Ahmad Tajudin
الملخص: علاج التهاب القزحية الأمامية المتكرر بعد العملية الجراحية أمر صعب. نقدم هنا تقريرا عن معالجة ناجحة لحالتين بالحقن التجويفي لمنشط البلازمينوجين النسيجي المركب في حالتين من حالات التهاب القزحية الأمامية المتكرر؛ حالة التهاب القزحية الأمامية المعدي وحالة " فوت-كويناقي-هرادا". أُصيبت سيدة في الأربعين من العمر باحمرار في العينين وضعف الرؤية لمدة أسبوعين. كان لديها التهاب القزحية الأمامية، والتهاب الأوعية الدموية، والتهاب الشبكية، وتورم القرص البصري. وكانت اختبارات الأمصال لبكتريا بارتونيلا هنسيلي وتوكسوبلازما جوندياي موجبة. تم علاجها بالكورتيكوستيرويدات العامة على المدى الطويل والمضادات الحيوية المناسبة. كانت حالتنا الثانية رجلا سليما يبلغ من العمر ٣٠ عاما ظهر لديه احمرار غير مؤلم في العينين مع ضعف في الرؤية وصداع وطنين لمدة أسبوعين. كان هناك التهاب حبيبي في العينين مع التهاب السائل الثقيل والكورويد والشبكية مع احمرار القرص البصري. وتم تشخيصه على أنه حالة " فوت-كويناقي-هرادا" وتم علاجه بالكورتيكوستيرويدات العامة. نتج لدى الحالتين إعتام ثانوي في عدسة العين والماء الأزرق الذي استدعي التدخل الجراحي. أدى الالتهاب المزمن المستمر إلى تكوين غشاء ليفي سميك أمام العدسة بعد جراحة استحلاب العدسة مع زراعة عدسة جديدة. بعد ذلك أُزيل الغشاء جراحيا وتلى ذلك الحقن التجويفي لمنشط البلازمينوجين النسيجي المركب بجرعة ٢٥ ميكروغرام. كان هناك تشافي للالتهاب المستمر وتحسن كبير في حدة البصر في غضون أسبوع من الحقن. لم تُسجل أي تأثيرات جانبية في العين أو في الجسم. الحقن التجويفي لمنشط البلازمينوجين النسيجي المركب مفيد في المرضى الذين يعانون من التهاب القزحية الأمامية المتكرر بعد العملية الجراحية. في معظم الحالات، يكون التدخل الجراحي مهما لتوفير رؤية يستفيد منها المريض. يجب أن يؤخذ الحقن التجويفي لمنشط البلازمينوجين النسيجي المركب في الاعتبار عند التعامل مع الالتهابات المستمرة من أسباب مختلفة. Abstract: Management of inflammation after surgery for recalcitrant anterior uveitis is challenging. Herein, we report successful treatment using intracameral injection of recombinant tissue plasminogen activator (rtPA) in two patients with recalcitrant anterior uveitis, due to infective uveitis and Vogt–Koyanagi–Harada disease, respectively. A 40-year-old woman presented with bilateral redness and vision reduction that had persisted 2 weeks. She also had bilateral anterior uveitis, vasculitis, retinitis, and optic disc swelling. Serology was positive for Bartonella henselae and Toxoplasma gondii . She was treated using long-term systemic corticosteroids and appropriate antibiotics. Our second case; a healthy 30-year-old man with bilateral eye redness and reduced vision without pain, and associated with headache and tinnitus for 1 weeks. He showed bilateral granulomatous inflammation with vitritis, choroiditis, retinitis, and hyperemic optic disc. The patient was diagnosed with Vogt-Koyanagi-Harada disease and treated with systemic corticosteroids. Both patients developed secondary cataracts and glaucoma that necessitated surgical intervention. Persistent chronic inflammation led to the formation of a thick fibrin membrane anterior to the intraocular lens (IOL) after phacoemulsification surgery with IOL implantation. This membrane was removed surgically, and intracameral injection of rtPA (25 μg) was carried out. The persistent inflammation had resolved and visual acuity had significantly improved within 1 week of intracameral rtPA injection. There were no reported ocular or systemic side effects. Intracameral rtPA is beneficial in patients with recalcitrant anterior uveitis who have undergone intraocular surgery. In most cases, surgical intervention improves the patients' vision. Intracameral rtPA should be considered in cases of persistent inflammation of varying etiology.